Addition of aceh bentonite in an effort to improve the heat resistance properties of polyurethane-based paint coatings - Ilyas Yusuf; M. Yunus; Teuku Rihayat; Sabila Yasara SA; Nurhanifa Aidy (Jurnal POLIMESIN, 2023)
Polyurethane is a polymer compound whose main chain constituent is urethane group (-NHCOO-). Polyurethanes can be mixed with other polymers or other fillers in an effort to enhance and improve the properties of the single polymer. Metal coating materials are needed for metal materials that have properties resistant to heat thermal condition and corrosion that can damage the structure,. The priority and novelty of this research is to utilize the natural bentonite which is very potential in the local area to fill polyurethane-based coating paint in order to improve its properties. This research looked at the effect of mixing Polyurethane with Bentonite filler obtained from Nisam, North Aceh which has been modified with CTAB and AgNO3 surfactants. The sample formulation used is polyurethane and polyurethane with North Aceh Bentonite variations of 1.5, 2.5, and 3.5%. Characterization with the addition of Bentonite produces polymers that have good thermal stability capabilities. The addition of Bentonite filler into polyurethane polymer can affect the mechanical properties of the material. The Polyurethane/Bentonite composite sample has better thermal resistance, where in pure Polyurethane, the initial weight reduction of the pure Polyurethane sample is 50-150 ℃, the decomposition of pure Polyurethane is at 385 ℃. For Polyurethane/Bentonite 98.5:1.5% w/w nanocomposite, the initial weight reduction is 150-300 ℃, decomposition at 416 ℃. For Polyurethane/Bentonite 97.5:2.5 w/w, the initial weight reduction is 150-250 ℃ and decomposition at 430 ℃. Polyurethane/Bentonite 96.5:3.5 w/w initial weight reduction is also at 200-300 ℃ and decomposition at 458 ℃.